13 Incidence and predictors of pulmonary nodules and other significant extra-coronary findings found on ct coronary angiography: a prospective analysis of an unselected irish population in a single centre. (5th October 2017) - Traynor, B; Naimimohasses, S; Khan, I; Slattery, J; Logan, H; Cosgrave, J
Abstract : Introduction: CT coronary angiography (CTCA) has become the cornerstone in the diagnosis of coronary artery disease (CAD). Cardiologists need to be aware of the prevalence and importance of extra-coronary findings, of which pulmonary nodules are the most commonly encountered. Aim: To determine the incidence and predictors of significant extra-coronary findings on CTCA in an unselected prospectively recruited Irish population. Methods: All patients undergoing CTCA in the Midlands Regional Hospital Mullingar between May 2011 and April 2016 were included in a prospective database. CTCAs were performed using a standard departmental protocol. All patients had calcium scoring performed and, if heart rate and rhythm were suitable, had coronary angiography. All CTCAs were joint reported by experienced consultant radiologists and cardiologists. Pulmonary nodules were categorized according to the Fleischner guidelines. We also recorded all other significant extra-coronary findings reported. Data was analysed using chi-square and Mann-Whitney u tests using SPSS Statistics. Results: A total of 693 patients were included. 181 (26.1%) of these patients were found to have a significant extra-coronary finding on CTCA, of which 79 (11.4%) were pulmonary nodules. Other significant findings included non-nodule pulmonary findings (73), gastrointestinal (17), mediastinal (5), cardiac (4), and breast findings (3). There were no statistically significant predictors of the presence of pulmonary nodules identified in terms of age, sex and multiple cardiac risk factors including smoking history. (Table 1) Conclusion: Significant pulmonary and non-pulmonary findings are commonly encountered during CTCA. Standard risk factors, including smoking, do not seem to predict the presence of pulmonary nodules. These findings emphasise the importance of a joint reporting system between cardiologists and radiologists in the interpretation of CTCA.